Additive manufacturing to assist prosthetically guided bone regeneration of atrophic maxillary arches. Issue 6 (19th October 2015) - Fantini, M.; De Crescenzio, F.; Ciocca, L.; Persiani, F.
Abstract : Purpose: – The purpose of this paper is to describe two different approaches for manufacturing pre-formed titanium meshes to assist prosthetically guided bone regeneration of atrophic maxillary arches. Both methods are based on the use of additive manufacturing (AM) technologies and aim to limit at the minimal intervention the bone reconstructive surgery by virtual planning the surgical intervention for dental implants placement. Design/methodology/approach: – Two patients with atrophic maxillary arches were scheduled for bone augmentation using pre-formed titanium mesh with particulate autogenous bone graft and alloplastic material. The complete workflow consists of four steps: three-dimensional (3D) acquisition of medical images and virtual planning, 3D modelling and design of the bone augmentation volume, manufacturing of biomodels and pre-formed meshes, clinical procedure and follow up. For what concerns the AM, fused deposition modelling (FDM) and direct metal laser sintering (DMLS) were used. Findings: – For both patients, a post-operative control CT examination was scheduled to evaluate the progression of the regenerative process and verify the availability of an adequate amount of bone before the surgical intervention for dental implants placement. In both cases, the regenerated bone was sufficient to fix the implants in the planned position, improving the intervention quality and reducing the intervention time during surgery. Originality/value: – A comparison between two novel methods, involving AM technologies are presented as viable and reproducible methods to assist the correct bone augmentation of atrophic patients, prior to implant placement for the final implant supported prosthetic rehabilitation.